Men at higher risk of groin injuries in elite team sports: a systematic review - Orchard, J. W. (British Journal of Sports Medicine, 2015)
Background: Groin injuries are common in sports, particularly multidirectional team sports, but incidence rates across sports other than football (soccer) have been poorly documented. Methods: A systematic review (initially using PubMed and SportDiscus databases) was performed to record incidence of groin and groin region injuries in sports. Inclusion criteria included presentation of groin injury incidence data for at least 10 team/squad seasons. Results: Data from 31 studies were included. These used varying injury definitions and also considered varying injury categories from general to specific (all groin/hip region injuries, groin injuries, adductor muscle strains, intra-articular hip injuries). When playing the same sport, men had greater injury incidence of groin injury than women (relative risk, RR 2.45, 95% CI 2.06 to 2.92). Sports with high incidences of groin injury included ice hockey and the football codes. There is variation by player position for rate of groin injury in many sports. Hip injuries have become more commonly diagnosed over the past decade in Australian football (p=0.001) and other sports. Conclusions: There is moderate evidence that men have a higher risk of groin injury than women when playing the same sport. There is some evidence that hip injuries are being increasingly diagnosed in the subset of `groin injuries` in recent years. It is recommended that injury epidemiology consensus statements aim to include a number of relevant sports to improve injury incidence comparisons among different sports.